2023
DOI: 10.1021/acssuschemeng.2c06621
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Amine-Anchored Triazine-Based Covalent Organic Polymers for Selective CO2 Adsorption and Conversion to Cyclic Carbonates Under Mild Conditions

Abstract: Attaining both large uptake and high conversion of CO2 under mild reaction conditions within a metal-free covalent organic polymer (COP) is an attractive and challenging strategy for CO2 utilization because CO2 is an abundant and renewable C1 source and a main greenhouse gas. In this study, novel amine-anchored covalent triazine aromatic polymers (CTP-1-NH2 and CTP-2-NH2) were synthesized from 2-amino-4,6-dichloro-1,3,5-triazine, biphenyl, and 1,3,5-triphenylbenzene via facile Friedel–Crafts arylation for CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 94 publications
(127 reference statements)
1
10
0
Order By: Relevance
“…On the contrary, BO with electron-pushing substituents has the same high conversion as PO. In addition, the conversion of internal epoxides CHO and VCHO is relatively low due to the high resistance of their own structures. , We found that all epoxides maintained a selectivity of more than 96% for the formation of CCs, which proved that the Zn-HUT4/TBAB catalytic system was applicable in the selective formation of CCs. Moreover, in Table , we compared the catalytic performance of several M-POP catalysts in recent years.…”
Section: Results and Discussionmentioning
confidence: 70%
“…On the contrary, BO with electron-pushing substituents has the same high conversion as PO. In addition, the conversion of internal epoxides CHO and VCHO is relatively low due to the high resistance of their own structures. , We found that all epoxides maintained a selectivity of more than 96% for the formation of CCs, which proved that the Zn-HUT4/TBAB catalytic system was applicable in the selective formation of CCs. Moreover, in Table , we compared the catalytic performance of several M-POP catalysts in recent years.…”
Section: Results and Discussionmentioning
confidence: 70%
“…The N 2 adsorption capacity at 273.15 K/1.0 bar is 0.61 mmol/g, and CH 4 adsorption capacities at 273.15 K/1.0 bar and 298.15 K/1.0 bar are 1.57 and 1.14 mmol/g, respectively. The adsorption data of CH 4 at 273.15 K/1.0 bar are higher than those of some materials prepared in the past two years, such as SNNU-5-Sc (1.21 mmol g −1 ), CNOP-2 (1.37 mmol g −1 ), CTP-1-NH 2 (1.50 mmol g −1 ), and MOF-2 (0.63 mmol g −1 ) . Moreover, we also gained important data about the separations of CO 2 from N 2 and CH 4 .…”
Section: Resultsmentioning
confidence: 80%
“…Similar open-loop hysteresis behaviors have been previously reported for several hypercross-linked polymers with narrow-sized pores. 18,22,23 BETspecific surface area (SA BET ) of TPPM was measured to be 1120 m 2 g −1 (BET linear plot shown in Supporting Information, Figure S1). TPPM exhibited a total pore volume (V tot ) of 0.650 cm 3 g −1 and a micropore volume (V mic ) of 0.445 cm 3 g −1 (Table 1).…”
Section: Textural Properties Of Tppmmentioning
confidence: 99%